A high-quality genetic reference database for European commercial fishes reveals substitution fraud of processed Atlantic cod (Gadus morhua) and common sole (Solea solea) at different steps in the Belgian supply chain. (July 2020) - Deconinck, Dumas; Volckaert, Filip A.M.; Hostens, Kris; Panicz, Remigiusz; Eljasik, Piotr; Faria, Miguel; Monteiro, Carolina Sousa; Robbens, Johan; Derycke, Sofie
Abstract: Seafood is an important component of the human diet. With depleting fish stocks and increasing prices, seafood is prone to fraudulent substitution. DNA barcoding has illustrated fraudulent substitution of fishes in retail and restaurants. Whether substitution also occurs in other steps of the supply chain remains largely unknown. DNA barcoding relies on public reference databases for species identification, but these can contain incorrect identifications. The creation of a high quality genetic reference database for 42 European commercially important fishes was initiated containing 145 Cytochrome c oxidase subunit I ( COI ) and 152 Cytochrome b ( cytB ) sequences. This database was used to identify substitution rates of Atlantic cod ( Gadus morhua ) and common sole ( Solea solea ) along the fish supply chain in Belgium using DNA barcoding. Three out of 132 cod samples were substituted, in catering (6%), import (5%) and fishmongers (3%). Seven out of the 41 processed sole samples were substituted, in wholesale (100%), food services (50%), retailers (20%) and catering (8%). Results show that substitution of G. morhua and S. solea is not restricted to restaurants, but occurs in other parts of the supply chain, warranting for more stringent controls along the supply chain to increase transparency and trust among consumers. Highlights: A DNA reference database for commercially important European fish species was created, with cytB and COI sequences. The Belgian fish supply chain was mapped out and revealed 11 categories of fish trade. DNA barcoding and qPCR identified low levels of substitution in Gadus morhua . DNA barcoding revealed a high substitution rate in Solea solea, which was mostly substituted by Limanda aspera . Substitution occured throughout the entire fish supply chain.